Extending the Applications of Recent Real-Time Heuristic Search - Huntley, Daniel; Bulitko, Vadim (Proceedings of the AAAI Conference on Artificial Intelligence, 2011)
Real-time heuristic search algorithms that precompute search space-specific databases have demonstrated exceptional performance in video-game pathfinding. We discuss the first steps towards extending these algorithms to other search spaces that also benefit from the real-time property. We present our initial progress in characterizing the performance of current algorithms based on the features of a search space, and discuss future directions of this research.